Social Loafing and Group Performance: A Literature - Pandeirot, Lanemey B.; Aseng, Andrew C. (11th International Scholars Conference, 2017)
In a group, each member has his or her own personal interest and often there will be one or two group members that tend to reduce their job performance should the work with others in a group, compared to work individually. This behavior is widely known as social loafing. Thus, this study aims to examine the impact of social loafing on group performance and productivity. Reviews from literatures and articles are done to collect and study this impact. The majority of studies found bad impact of social loafing on group performance as well as group productivity. Yet, some previous studies suggested positive things about social loafing. This study also discusses about the advantages and disadvantages of social loafing, then how to reduce or even prevent this behavior happens in a group.